Analysis of the psychometric properties of the Malay version of beck depression inventory II (BDI-II) among postpartum women in Kedah, North West of Peninsular Malaysia - Wan Mahmud, Wan Mohd Rushidi; Awang, Amir; Herman, Iran; Mohamed, Mahmood Nazar (Universiti Sains Malaysia, 2004)
Increased international collaboration in clinical trials has created a need for cross culturally valid instruments to assess the quality of life and behavioural disorders. Cross cultural studies of depressive symptomatology, in particular, must be preceded by an exhaustive study of the psychometric properties of the instruments to ensure the validity of the comparison. In this article, we examined the validity, reliability and factor structure of the Malay version of the Beck Depression Inventory II (BDI-II) among Malay postpartum women attending selected health centres in Kedah, North West of Peninsular Malaysia. Our findings indicated that the current version of the BDI-II is psychometrically strong and appropriate for use in assessing depressive symptomatology among this group of women.